PENINGKATKAN HASIL BELAJAR IPS MENGGUNAKAN MEDIA GAMBAR BAGI SISWA KELAS IV SEKOLAH DASAR - Safrudin Safrudin; Abdul Putra Ginda Hasibuan (JURNAL PENDIDIKAN ROKANIA, 2016)
This study aims to improve learning outcomes IPS by using media images to the fourth grade students of SD Negeri 008 Tanjung Alam District of Fullness of Rokan Hulu. The method used was classroom action research model Mc Kemmis hashtag. The results showed that there was an increase in the results of social studies class IV SDN 008 Desa Tanjung Alam Fullness Fullness Eastern District of learning outcomes pratindakan current class average is 65.76, for completeness there are 12 students or 48% and was not finished there are 13 students or 52 %